Land value capture to promote local development in Baltics: a comparative study of Estonia, Latvia and Lithuania - Jürgenson, Evelin; Auziņš, Armands; Burinskienė, Marija (International Conference “Environmental Engineering”, 2017)
By capturing value increase, it should be used for specific purposes in the way that would support implementation of infrastructure projects and promote local development. Accordingly, the stakeholders’ interests have to be balanced and fair decision-making promoted. The research emphasises on comparative analysis of Estonian, Latvian and Lithuanian experiences in covering development costs and absorbing value increase. The purpose of the study is to give an overview of the land value capture as well as to discuss how it promotes local development and what is an institutional environment supporting it in three Baltic countries with similar historical evolution during last two decades. The functions of local authorities and spatial planning systems have been analysed in the study. The comparative analysis and synthesis, the logical-constructive and graphical methods mainly are used for the research. Direct and indirect models, which are used for the absorption of the surplus value of developed land, have been observed in the study. The outcome of the research shows an interim conclusion for Estonia, Latvia and Lithuania, and it may contribute to comparative analysis in larger – European context – in order to get an overview of land value capture across Europe.
Keywords: land value capture; local development; comparative study; Baltic countries